Audit methodology for the quality assessment of medical records in the emergency department. (30th September 2020) - Chiappa, F; Vigezzi, G P; Salvati, S; Scardoni, A; Oradini Alacreu, A; Zandalasini, C; Sancini, S; Odone, A; Signorelli, C
Abstract: Issue: Filling out medical records properly in Emergency Departments (ED) can be challenging, due to the high number of daily admissions and the variety of involved health care professionals (HCP). Description of the Problem: The ED of IRCCS San Raffaele Hospital (OSR), with a mean of 198 admissions per day in 2019, suffers of frequent overcrowding; patients are managed by multiple HCPs, based on specific care needs; coordination and handover between them are crucial to guarantee quality care. The OSR Healthcare Directorate, the ED's Staff and the School of Public Health of Vita-Salute San Raffaele University developed and validated a model of internal audit to identify ED medical records' quality issues and to implement corrective actions. The workflow included: developing a structured checklist, mapping critical processes and highlighting each figure's tasks. A group of auditors, made up by medical residents in Public Health, tested n = 300 medical charts, filled out during the first semester of 2019, picked up in order to provide a representative sample of the triage priority codes assigned to patients in this period. Results: To assess completeness and quality of ED's medical records, a new checklist was developed, comprising 4 major sections, furtherly divided in 14 items, scored from 1 (poor adherence/completeness) to 5 (excellent), providing a total score for each record, ranging from 14 to 70. Specific comments to items could be added and an ultimate judgement was written by each auditor. This approach made medical records measurable and comparable. Lessons: The new checklist and the audit process are useful instruments for the evaluation of medical records and the identification of corrective measures in the ED of our hospital. Next steps will be the extension of the sample, the implementation of corrective actions, and the institution of a stable working group for a regular evaluation. Key messages: ED's medical records must be clear, understandable and complete. The developed checklist is a tool for preventing and correcting wrong behaviours in a continuous improvement perspective.